The philosophy of law and legal science - Zakhart͡sev, S. I. (Sergeĭ Ivanovich), 1976-; Salʹnikov, V. P. (Cambridge Scholars Publishing, 2018)
The book explores a variety of problems connected to philosophy and philosophy of law. It discusses the problem of monism-pluralism in philosophy and philosophy of law, criticizes philosophy of post-positivism and postmodernism, and investigates dialectics as a universal global methodological basis of scientific cognition and philosophy of law. The volume also pays particular attention to contemporary legal education, offering potential solutions to problems in this field. The book is the result of a range of sociological studies conducted both in Russia and abroad concerning the legal process.